Religious Publishing and Print Culture in Modern China: 1800-2012 - Clart, Philip; Scott, Gregory Adam (Religion and society, 2015)
Biographical note: Philip Clart, Universität Leipzig, Deutschland;Gregory Adam Scott, Universität Edinburgh, UK.